Acorenone C: A New Spiro-Sesquiterpene from a Mangrove-Associated Fungus, Pseudofusicoccum sp. J003 - Jia, Shujie; Su, Xiangdong; Yan, Wensi; Wu, Meifang; Wu, Yichuang; Lu, Jielang; He, Xin; Ding, Xin; Xue, Yongbo (Frontiers in Chemistry, 2021)
Mangrove-derived endophytes are rich in bioactive secondary metabolites with variety of biological activities. Recently, a fungus Pseudofusicoccum sp. J003 was firstly isolated by our research group from mangrove species Sonneratia apetala Buch.-Ham. The subsequent chemical investigation of the methanol extract of the culture broth of this strain has led to the isolation of a new sesquiterpenoid named acorenone C (1), two alkaloids (2–3), four phenolic compounds (4–7), and four steroid derivatives (8–11). The new structure of 1 was established by extensive spectroscopic analysis, including 1D, 2D NMR spectroscopy and HRESIMS. Its absolute configuration was elucidated by experimental ECD and ECD calculation. The in vitro AChE inhibitory, anti-inflammatory, and cytotoxic activities of the selected compounds were evaluated. The results showed that compound 1 showed mild AChE inhibitory activity with an inhibition rate of 23.34% at the concentration of 50 μM. Compound 9 exerted significant inhibitory effect against nitric oxide (NO) production in LPS-stimulated RAW 264.7 mouse macrophages, with an inhibition rate of 72.89% at the concentration of 25 μM, better than that of positive control L-NMMA. Compound 9 also displayed obvious inhibition effects on the growth of two human tumor cell lines HL-60 and SW480 (inhibition rates 98.68 ± 0.97% and 60.40 ± 4.51%, respectively). The antimicrobial activities of the compounds (1–11) against Escherichia coli, Bacillus subtilis, Staphylococcus aureus, and Pseudomonas aeruginosa were also tested, however, none of them showed antimicrobial activities.